Designing Diverse Agricultural Pastures for Improving Ruminant Production Systems - Distel, Roberto A.; Arroquy, José I.; Lagrange, Sebastián; Villalba, Juan J. (Frontiers in Sustainable Food Systems, 2020)
Pasture-based production systems represent a significant sustainable supplier of animal source foods worldwide. For such systems, mounting evidence highlights the importance of plant diversity on the proper functioning of soils, plants and animals. A diversity of forages and biochemical-primary and secondary compounds- at appropriate doses and sequences of ingestion, may lead to benefits to the animal and their environment that are greater than grazing monocultures and the isolated effects of single chemicals. Here we review the importance of plant and phytochemical diversity on animal nutrition, welfare, health, and environmental impact while exploring some novel ideas about pasture design and management based on the biochemical complexity of traditional and non-traditional forage sources. Such effort will require an integration and synthesis on the morphology, ecophysiology and biochemistry of traditional and non-traditional forage species, as well as on the foraging behavior of livestock grazing diverse pasturelands. Thus, the challenge ahead entails selecting the “right” species combination, spatial aggregation, distribution and management of the forage resource such that productivity and stability of plant communities and ecological services provided by grazing are enhanced. We conclude that there is strong experimental support for replacing simple traditional agricultural pastures of reduced phytochemical diversity with multiple arrays of complementary forage species that enable ruminants to select a diet in benefit of their nutrition, health and welfare, whilst reducing the negative environmental impacts caused by livestock production systems.